Pseudo-volunteering in wartime: a topical issue of today (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The present study attempts to provide a scientific interpretation of volunteering, and considers the practical significance of the database “Register of Volunteers of Ukraine” in terms of recording and accumulating information on persons who provide free assistance to people affected by the war and the Armed Forces of Ukraine. For the purpose of a complete and comprehensive study, a number of current regulatory legal acts have been studied, in particular, laws of Ukraine, certain articles of the Criminal Code of Ukraine, which directly or indirectly contain both the interpretation of the concepts under study and provide a wide range of scientific and legal tools necessary for studying the issues raised. The relevance of the topic under study is illustrated by a number of specific examples of volunteer activities carried out within the requirements and provisions of current legislation, as well as examples of actions of pseudo-volunteers which are outside the scope of legislative regulation. An attempt has been made to systematise the most significant bottlenecks and gaps in the legislative regulation of volunteer activities, which are used by pseudo-volunteers to abuse the trust of individuals and legal entities, undermining one of the most important foundations of our society – people’s trust in each other. The results of the study are formulated in the form of a substantiated conclusion and proposals are made in terms of exploring the possibilities of preparing, discussing and, if supported, amending the current legislation that directly regulates and governs volunteer activities, as well as establishing additional preventive mechanisms designed to prevent abuse in this area. The unity of efforts of state bodies and institutions, combined with the free will of citizens and public organisations in carrying out open volunteer activities, providing assistance and assistance based solely on the call of the heart, openness and trust, can withstand all the challenges facing our country today by providing comprehensive support to the affected category of citizens and strengthening Ukraine's defence capabilities.